Language contact and world Englishes. Issue 2 (June 2016) - ONYSKO, ALEXANDER
ABSTRACT: Language contact has continued to play a role in world Englishes research, but its potential for analyzing Englishes and for mapping their diversity has not yet been applied in a comprehensive manner. This introduction to the special issue addresses different facets of the connection between language contact and world Englishes. The seven articles of the special issue are briefly outlined, showing the relevance of taking a contact linguistic approach to understanding world Englishes both from a theoretical and an empirical point of view.